Using Mobile Phone Texting to Support the Capacity of School Leaders in Ghana to Practise Leadership for Learning - Swaffield, Sue; Jull, Stephen; Ampah-Mensah, Alfred (Procedia - Social and Behavioral Sciences, 2013)
Several years into a collaborative professional development programme to build the Leadership for Learning capacity of Basic school headteachers throughout Ghana, the challenge is to sustain commitment, deepen understanding and share learning among the school leaders. Employing ubiquitous mobile phone technology, weekly text messages have been sent to the programme's 175 initial participants. During the year of the pilot project different forms of messages have been tried, and feedback from recipients suggests their value. The paper reports experience and findings from the pilot, and considers plans for scaling-up to reach all 18,000 Basic schools across the country.
Keywords: Ghana; Leadership for Learning; SMS; headteachers; mobile phone; professional development; school leaders; text messages

eTransform Ghana Project Appraisal Document - World Bank (2013)

Complementary Education Programme (CEP) and the Opportunity to Learn In the Northern Region of Ghana - Arkorful, Kingsley K D (University of Sussex, 2013)

Examining the impact of Information and Communication Technology capacity building in High School education in Ghana. - Abilimi, Chris; Adu-Manu, Kofi S. (International Journal of Engineering Research & Technology (UER), 2013)
The quality of education in general is improved, if Information and Communication Technology (ICT) is used in teaching and learning in High School education. This is because the use of ICT related strategy for teaching and learning rise the
Keywords: ⛔ No DOI found

Empowering teachers and children for a healthy digital life : report on activities carried out at the European School of Varese, Italy. - European Commission (2013)
This document reports on a training action with teachers that targeted mostly the role of teachers in the promotion of a balanced and healthy online life and the prevention of cyber-bullying at primary school level. Our aim in this experience in training the primary teacher of the European School of Varese is to open a path to empower teachers in guiding our children to become smart, responsible, and respectful also when using media and help them to understand the ethical consequences behind the decisions they make online. Healthy children learn better and become healthy adults enabling them to reach their potential. This document describes the training activities that took place among teachers of the primary sections of the European School of Varese. It then summarises the observations made by the moderators of the respective activities and finally presents the recommendations that have been made by the teachers and the moderators in the light of the described experiences.

An Infographic Presentation of Eneza's 2012 Impact Study - Eneza Education (Eneza Education, 2013)
I am sure you are wondering what Eneza is, that should not worry you at all. We have just changed our name from MPrep to Eneza. “Eneza” is a Swahili ... Read More

Improving teaching and learning of basic maths and reading in Africa: Does teacher preparation count? - Akyeampong, Kwame; Lussier, Kattie; Pryor, John; Westbrook, Jo (International Journal of Educational Development, 2013)
Teacher education has an important role in ensuring quality of learning especially for the poorest children. The article draws on a study of teacher preparation for the early primary grades in six African countries – Ghana, Kenya, Mali, Senegal, Tanzania and Uganda – in reading and mathematics. Initial teacher education had the strongest impact on newly qualified teachers but also induced misplaced confidence leading to standardised teacher-led approaches that failed to engage learners. Learning to read was divorced from meaning while mathematical activities were not linked to learning concepts. We suggest that teacher education is reconstructed as a study of classroom practice that places children's learning at its centre.